A Parametric Study of Higher-Mode Natural Frequencies of Composite Stiffened Cylindrical Shell With Cut-Out - BASU CHAUDHURI, Puja; MITRA, Anirban; SAHOO, Sarmila (Engineering Transactions, 2023)
A finite element-based dynamic study of cut-out borne composite cylindrical shells reinforced with stiffeners is conducted. Isoparametric shell element with eight nodes and beam element with three nodes are used to study the mode-frequency behavior of shells with varied edge conditions. Anti-symmetric angle-ply laminates of two, four and ten layers with varying lamination angles are considered. Ten-layer laminates are investigated further as they exhibit better performance in fundamental frequency than two and four-layer laminates. The reduced integration method is adopted to find the shell element’s stiffness and mass matrices and the subspace iteration method is used for the eigenvalue solution of free vibration formulation. Natural frequencies for the first five modes are considered. The effects of fiber orientation angle (θ), degree of orthotropy (E11/E22), and width/thickness ratio (b/h) on the natural frequency are determined through numerical studies. It is revealed that vibration behavior strongly depends on both the number and arrangement of boundary constraints.